Persepsi pengguna e-Repository di Badan Tenaga Nuklir Nasional - Noeraida Noeraida; Budi Prasetyo; Rochani Nani Rahayu; Andri Sungkono; Anggiana Rohandi Yusuf; Iis Sustini; Nadifa Salsabila (Jurnal Kajian Informasi dan Perpustakaan, 2021)
The establishment of an institutional repository is to store intellectual assets in digital form in a single repository to facilitate retrieval, provide open access to promote scientific work produced, and detect plagiarism. The National Nuclear Energy Agency (BATAN) developed the institutional repository as an e-Repository, to save research results; however, the use of e-Repository by users has decreased. This study aimed to determine the perception of e-Repository users in the National Nuclear Energy Agency. The study used a descriptive research method through a quantitative approach. Using a stratified sampling technique, research respondents were 349 people from a total population of 1,148 users. The results showed that respondents who knew the term repository were 13.90%, e-Repository was 19.35%, and 5,18% saved documents to e-Repository. The willingness of respondents to use e-Repository and deposit their work was 29.38%, respondents who did not know but would deposit their work was 51.49%. User's understanding of the types of library materials stored in the e-Repository were articles published in journals was 47.19%. At the same time, respondents who understood the purpose and benefits of e-Repository were 54.82%. Users did not save documents to the e-Repository because they doubted the security was 25.71%. The study concludes that the respondents do not fully believe in the security of the data stored in the BATAN e-Repository. However, they realize that it will be easier to retrieve documents stored in the e-Repository.